Failing forward in Eastern Enlargement: problem solving through problem making. Issue 7 (3rd July 2022) - Anghel, Veronica; Jones, Erik
ABSTRACT: The 'failing forward' synthesis of liberal intergovernmentalism and neofunctionalism puts European member states governments in charge of the process of integration (Jones et al., [2016]. Failing Forward? The Euro Crisis and the Incomplete Nature of European Integration. Comparative Political Studies, 48(7), 1010–1034. https://doi.org/10.1177/0010414015617966). However, this placement does not show clearly whether the principals are reactive or proactive. That distinction between proactive and reactive is important in understanding what it means to say that integration is a movement 'forward' and what we mean by 'success'. Moving forward could mean building out the great ideals of Europe's political leaders, but it could also mean reacting to events in a way that solves problems, even if only imperfectly. The process of Eastern enlargement shows this distinction at work. We argue that enlargement is 'successful' as a reactive process and not as a proactive one. In proactive terms, the Eastern enlargement process has a consistent record of failure inasmuch as agents did not get what they wanted when they wanted it. In reactive terms, enlargement contributed to the creation of a wider and a deeper European Union.